Writing Inspirational Stories: A Needs Analysis of Prospective Indonesian Language Teacher Students - Adi Rustandi; Nani Solihati; Wini Tarmini (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
The ability to write inspirational stories constitutes an essential aspect of the pedagogical competence of prospective Indonesian language teachers. However, empirical evidence indicates that this type of narrative writing has not received sufficient attention within teacher education curricula, resulting in various internal and external challenges. This study aims to provide an in-depth needs analysis by examining the barriers, opportunities, challenges, and instructional model development encountered by prospective Indonesian language teachers in writing inspirational stories. Employing a qualitative descriptive-narrative approach, data were collected through in-depth interviews, participant observation, and document analysis involving students of an Indonesian Language Education program at a public university in Indonesia. The findings reveal that the primary barriers stem from low self-efficacy, limited philosophical understanding of the concept of “inspirational,” and insufficient engagement in reflective writing practices during their academic training. Meanwhile, opportunities emerge through experience-based training, creative mentoring, and the implementation of storytelling practices in authentic contexts. The major challenge lies in the misalignment between professional practice demands and curriculum design, which tends to prioritize academic aspects over practical competencies. Therefore, the development of an instructional model for teaching writing is necessary to produce high-quality and meaningful texts. The study concludes that the most significant challenge is not merely technical, but rather rooted in prospective teachers’ limited conceptual understanding of the educational function of narratives. This study contributes theoretically to the development of a narrative framework in teacher education and offers practical implications through the integration of storytelling into the curriculum and training programs for prospective Indonesian language teachers.